ZAP-70 Shapes the Immune Microenvironment in B Cell Malignancies - Chen, Jingyu; Moore, Andrew; Ringshausen, Ingo (Frontiers in Oncology, 2020)
Zeta-chain-associated protein kinase-70 (ZAP-70) is a tyrosine kinase mainly expressed in T cells, NK cells and a subset of B cells. Primarily it functions in T cell receptor (TCR) activation through its tyrosine kinase activity. Aberrant expression of ZAP-70 has been evidenced in different B cell malignancies, with high expression of ZAP-70 in a subset of patients with Chronic Lymphocytic Leukemia (CLL), associating with unfavorable disease outcomes. Previous studies to understand the mechanisms underlying this correlation have been focused on tumor intrinsic mechanisms, including the activation of B cell receptor (BCR) signaling. Recent evidence also suggests that ZAP-70, intrinsically expressed in tumor cells, can modulate the cross-talk between malignant B cells and the immune environment, implying a more complex role of ZAP-70 in the pathogenesis of B cell malignancies. Meanwhile, the indispensible roles of ZAP-70 in T cell and NK cell activation also demonstrate that the autologous expression of ZAP-70 in the immune environment can be a central target in modulation of tumor immunity. Here we review the evidences of the link between ZAP-70 and tumor immunology in the microenvironment in B cell malignancies. Considering an emerging role of immunotherapies in treating these conditions, understanding the distinct molecular functions of ZAP-70 in a cellular context could ultimately benefit patient care.